Gynaecology and Obstetrics Medical Errors and Patient Safety - Tuğba Yılmaz Esencan; Ergül Aslan (Association of Nurse Managers, 2016)
Quality of nursing care is one of the most important and primary elements in the delivery of health care. With the improvement of the quality of nursing care, two most important issues of health services have been displayed: medical errors and patient safety. Patient death from medical errors is the eighth leading cause of death; higher than the number of deaths from traffic accidents, breast cancer, and AIDS. In addition to this, recent reports of 'The Institute of Medicine' have indicated that three out of twenty criteria necessary for quality medical services are related to patient safety. These areas are medication (drug) management, nosocomial infections, and elderly health. In terms of the rates of medical error, clinics of obstetrics are the source of most commonly diagnosed medical errors after surgical procedures. Gynaecology is a surgical area as well as a unit which diagnoses and treats obstetrics-related complex diseases. The risk of medical error is also high due to the higher number of elderly patients in gynaecology clinics. Therefore, patient safety in gynaecology clinics is among the issues that need improvement in healthcare services. Nurses are the ones who are in relation with patients' safety in all fields of health care. Many of the risks of medical errors in gynaecology clinics are related to nursing care and can be eliminated with safer nursing practices. In this context, patient safety practices in nursing services constitute an important part of care.